Role of inducibility and its dynamic change in the outcome of catheter ablation of atrial fibrillation: a single center prospective study. (23rd January 2020) - Darma, Angeliki; Daneschnejad, Sait S.; Gaspar, Thomas; Huo, Yan; Wetzel, Ulrike; Dagres, Nikolaos; Husser, Daniela; Sommer, Philipp; Piorkowski, Christopher; Bollmann, Andreas; Hindricks, Gerhard; Arya, Arash
Abstract: Background: The role of atrial arrhythmia inducibility as an endpoint of catheter ablation of atrial fibrillation (AF) has been a controversial subject in many studies. Our goal is to evaluate the significance of inducibility, the impact of multiple sites or protocols of stimulation or the change in inducibility status in a prospective study including patients with AF undergoing first catheter ablation. Methods: We studied 170 consecutive patients with AF (62.9% paroxysmal) undergoing catheter ablation. All patients underwent two separate stimulation protocols before and after the ablation from the coronary sinus ostium and the left atrial appendage: burst pacing at 300, 250, 200 milliseconds (or until refractoriness) for 10 seconds and ramp decrementing from 300 to 200 milliseconds in increments of 10 milliseconds every three beats for 10 seconds. Inducibility was defined as any sustained AF or organized atrial tachycardia (AT) lasting >30 seconds. Results: We had AF/AT inducibility in 55 patients at baseline compared to 36 following ablation. After a mean of 41, 3 months follow‐up, 115 patients were free of AF. Inducibility before or after the ablation or change in inducibility status did not influence AF recurrence. There were no significant differences regarding paroxysmal or persistent patients with AF. Conclusions: Non‐inducibility of atrial arrhythmia or change in inducibility status following pulmonary vein (PV) isolation and substrate modification are not associated with long‐term freedom from recurrent arrhythmia. Therefore, the use of induction of an endpoint in AF ablation is limited.